2011
DOI: 10.1007/s10529-011-0555-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a delta 6-desaturase gene from the black seabream (Acanthopagrus schlegeli)

Abstract: Delta 6-fatty acid desaturase (D6DES) is used in the synthesis of polyunsaturated fatty acids (PUFAs) from microorganisms to higher animals, including arachidonic acid (ARA) and eicosapentaenoic acid (EPA). A 1,338 bp full-length cDNA encoding D6DES was cloned from Acanthopagrus schlegeli (AsD6DES) through degenerate- and RACE-PCR methods. A recombinant vector expressing AsD6DES (pYES-AsD6DES) was subsequently constructed and transformed into Saccharomyces cerevisiae to test the enzymatic activity of AsD6DES t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Recently, some genes encoding FADS6 have been cloned and sequenced from many organisms ( 13,(20)(21)(22)(23)(24)(25)(26), but little is known about their molecular mechanism of FADS6 substrate preference. This is mainly due to the lack of crystal structure information.…”
Section: Site-directed Mutagenesis Of Mpfads6mentioning
confidence: 99%
“…Recently, some genes encoding FADS6 have been cloned and sequenced from many organisms ( 13,(20)(21)(22)(23)(24)(25)(26), but little is known about their molecular mechanism of FADS6 substrate preference. This is mainly due to the lack of crystal structure information.…”
Section: Site-directed Mutagenesis Of Mpfads6mentioning
confidence: 99%
“…At a molecular level, specific deficiencies in one or more enzymes, namely fatty acyl desaturases (Fads) with and elongases of very long-chain fatty acids (Elovl), involved in LC-PUFA biosynthesis underpin the abovementioned limitation in the biosynthetic capability of marine fish [1]. Studies have shown that the black seabream Acanthopagrus schlegelii , a commercially important species for intensive culture in China, Japan, Korea and other countries in Southeast Asia [5–11], possesses a Fads2 with Δ6 desaturase activity [12], as well as an Elovl5 with high efficiency for elongation of C 18 and C 20 PUFA [13]. …”
Section: Introductionmentioning
confidence: 99%
“…9) Over the past few decades, Á6-desaturase genes have been isolated from various organisms and characterized, including genes from cyanobacterium, 10) fungi, 11,12) plants, 13,14) and animals. 15,16) Furthermore, gene expression analysis has indicated that the transcript levels of Á6-desaturase genes in fungi increase under low temperature treatment, suggesting that these genes are involved in cold acclimation, 17,18) but the effect of environmental stresses on Á6-desaturase gene expression and their roles in stress responses have not been determined for higher plants.…”
Section: Identification and Functional Analysis Of A á6-desaturase Gementioning
confidence: 99%